Effect on health-related quality of life of a multimodal physiotherapy program in patients with chronic musculoskeletal disorders. - Cuesta-Vargas, Antonio; González-Sánchez, Manuel; Casuso Holgado, María Jesús (BMC, 2013)
Background: Musculoskeletal disorders are major causes of morbidity in the world, and these conditions have a strong negative influence in terms of health-related quality of life. The purpose of this study was to evaluate the effect of an 8-week multimodal physical therapy program on general health state and health-related quality of life in patients with chronic musculoskeletal disorders. Methods: There were 244 participants in this prospective cohort analysis with 8-week follow-up. The primary outcome was general health state (physical and mental components), determined with the Short Form-12 Health Survey (SF-12). The secondary outcome was health related quality of life, determined with the EuroQoL-5D and VAS. The intervention was evaluated by comparing pre- and post-outcome measurements. T-tests were performed for paired data. Results: Differences were statistically significant for physical health state: +1.68 (p < 0.05) (baseline: 42.38); mental health state: +3.15 (p < 0.001) (baseline: 46.57); and health related quality of life: +0.18 (EuroQoL 5D) (baseline: 46.57) and +7.22 (EuroQoL_VAS) (p < 0.001) (baseline: 60.81). Intervention resulted in clinically relevant changes in terms of percentage improvement from baseline scores. Conclusions: Eight weeks of a Multimodal Physical Therapy Program seemed to moderately enhance the general health state and HRQoL of patients with chronic musculoskeletal diseases. This kind of therapeutic exercise can be recommended to patients with chronic low back pain, chronic neck pain and osteoarthritis, at least in the short term.
Keywords: Aparato locomotor - Ejercicios terapéuticos; Chronic musculoskeletal disorders; Multimodal physiotherapy; Aquatic exercise; HRQoL